STRATEGI DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KOTA BEKASI DALAM MEMBANGUN KETAHANAN DAN KESEJAHTERAAN KELUARGA PERSPEKTIF HUKUM KELUARGA ISLAM - Basirrudin, Muhammad; Hambali, Yoyo; Supriyanto, Agus (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2024)
This study aims to identify the strategies for building family resilience and welfare by the Population Control and Family Planning Agency (DPPKB) of Bekasi City and to understand these strategies from the perspective of Islamic Family Law. This research employs a qualitative method with a socio-juridical approach and descriptive analysis techniques. The study reveals that family resilience and welfare are among the objectives of family formation in Islamic Family Law. In Islamic Family Law, family welfare is depicted in the concepts of Sakīnah, Mawaddah, and Raḥmah, generally referring to conditions of tranquillity, love, and compassion. Family resilience is also strongly emphasized with provisions regarding the rights and obligations of each family member, including the stipulations on divorce, which underscore the sanctity and strength of marital bonds. Divorce is considered highly undesirable in Islam, and guidelines for family life are provided, ranging from preparation for marriage to raising better future generations. The strategies employed by the DPPKB of Bekasi City in building family resilience and welfare align significantly with the values of Islamic Family Law, particularly in general aspects. However, in detail, these strategies do not fully encompass the comprehensive concepts of family formation and development as outlined in Islamic Family Law.